The Smithsonian first ladies collection - Graddy, Lisa Kathleen; Pastan, Amy; National Museum of American History (U.S.) (Washington, DC : Smithsonian Books, 2014)
"The Smithsonian First Ladies Collection is a beautifully illustrated book inspired by one of the most popular attractions at the Smithsonian: the first ladies exhibit at the National Museum of American History. This striking book showcases the treasures from first ladies throughout history, ranging from Martha Washington's silk dress and dressing mirror to Michelle Obama's 2009 inaugural gown and jewelry. These and many other unforgettable objects--including gowns, tableware, and invitations from beloved first ladies such as Mamie Eisenhower, Jacqueline Kennedy, Barbara Bush, Hilary Clinton, and more--tell the story of the first ladies as public and private figures. They illustrate how these women, thrust into an influential and visible role by happenstance of marriage, adapted themselves and the role of first lady by taking on responsibilities as campaigners, hostesses, and policy advocates. The Smithsonian First Ladies Collection features many treasures not on view at the exhibit. Complete with an insider's look at the acquisition, conservation, and exhibition of the pieces as well as a timeline of all forty-six first ladies, this is a must-have for anyone fascinated by these incredible women and their roles in American culture and political life"--
Includes bibliographical references.
Keywords: National Museum of American History (U.S.) -- Exhibitions; Presidents' spouses -- United States -- Biography -- Miscellanea; Presidents' spouses -- United States -- History -- Exhibitions; BIOGRAPHY & AUTOBIOGRAPHY / Presidents & Heads of State; BIOGRAPHY & AUTOBIOGRAPHY / Women; HISTORY / United States / General